Comparison between real-time dynamic substructuring and shake table testing techniques for nonlinear seismic applications. - Lamarche, C.-P.
Results from real-time dynamic substructuring (RTDS) tests are compared with results from shake table tests performed on a two-storey steel building structure model. At each storey, the structural system consists of a cantilevered steel column resisting lateral loads in bending. In two tests, a slender diagonal tension-only steel bracing member was added at the first floor to obtain an unsymmetrical system with highly variable stiffness. Only the first-storey structural components were included in the RTDS test program and a Rosenbrock-W linearly implicit integration scheme was adopted for the numerical solution. The tests were performed under seismic ground motions exhibiting various amplitude levels and frequency contents to develop first and second mode-dominated responses as well as elastic and inelastic responses. A chirp signal was also used. Coherent results were obtained between the shake table and the RTDS testing techniques, indicating that RTDS testing methods can be used to successfully reproduce both the linear and nonlinear seismic responses of ductile structural steel seismic force resisting systems. The time delay introduced by actuator-control systems was also studied and a novel adaptive compensation scheme is proposed.
Keywords: Real-time dynamic substructuring; Hybrid testing; Shake table testing; Rosenbrock; Benchmark; Delay compensation